2018
DOI: 10.1007/s10875-018-0564-1
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Hematopoietic Stem Cells for Primary Immunodeficiencies in Brazil: Challenges in Treating Rare Diseases in Developing Countries

Abstract: The results of hematopoietic stem cell transplant (HSCT) for primary immunodeficiency diseases (PID) have been improving over time. Unfortunately, developing countries do not experience the same results. This first report of Brazilian experience of HSCT for PID describes the development and results in the field. We included data from transplants in 221 patients, performed at 11 centers which participated in the Brazilian collaborative group, from July 1990 to December 2015. The majority of transplants were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
4
9
0
1
Order By: Relevance
“…The median age to transplant was 18 months, similar to other reports in the literature of HSCT in PID 9,10 . In this analysis, we did not find differences in patients who underwent HSCT before 12 months of age, previous studies in the field showed better survival when it was performed before 2 years of age, 4 either way, HSCT should be considered as soon as the diagnosis is made, since previous infections or organ damage can affect survival during the procedure.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The median age to transplant was 18 months, similar to other reports in the literature of HSCT in PID 9,10 . In this analysis, we did not find differences in patients who underwent HSCT before 12 months of age, previous studies in the field showed better survival when it was performed before 2 years of age, 4 either way, HSCT should be considered as soon as the diagnosis is made, since previous infections or organ damage can affect survival during the procedure.…”
Section: Discussionsupporting
confidence: 85%
“…We found no apparent benefit of combining 2 or more groups of medication for GVHD prophylaxis. As observed in our analysis, other studies also found no significant differences in GVHD according to donor type 9,26 …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…One possible explanation is that after haploidentical HSCT, subclinical graft versus host disease partially impairs thymus function. Nevertheless, recent advances in haploidentical HSCT (i.e., TCR αβ depletion, or even T cell–replete HSCT followed by the suppression of allogeneic T cells via in vivo cyclophosphamide treatment; Bertaina et al, 2014; Fernandes et al, 2018) may challenge this conclusion.…”
Section: Additional and Serendipitous Findingsmentioning
confidence: 99%